EFEK PUPUK CAIR KALSIUM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KENTANG (SOLANUM TUBEROSUM L.) - Donatus Dahang; Rafael Remit Winardi; Muhammad R.R. Lubis (Universitas Quality, 2019)
The research effects of liquid calcium fertilizers on the growing and producing of potatoes (Solanum tuberosum L.) had properly done. The research was carried out on Lau Gumba Village, Berastagi Sub-district, Karo Regency, North Sumatra, December 2018- May 2019. Randomize Block Design with two factors i.e. Faktor I: Concentration of “BF” fertilizer, B0: control, B1: 2, 5 ml/96 ml of water, B2: 5 ml/ 96 ml of water, B3: 7, 5 ml/ 96 ml of water. Factor II: concentration of “BC” fertilizer, C0: control, C1: 1 ml/ 96 ml of water, C2: 2 ml/ 96 ml of water, C3: 3 ml/ 96 ml of water. The results of the study show that the concentration of the liquid calcium fertilizer had significantly impact (p < 0.05) to the growing and the production of tubers. The concentration of B3 (7,5 ml/96 ml of water) and C3 (3 ml/96 ml of water) had highest score 39.4 cm of plants’ height, The concentration of B3 (7, 5 ml/96 ml of water) and C3 (3 ml/96 ml of water) had significant impact to tubers’ weight.